2019
DOI: 10.3390/molecules24193442
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Like Behavior for the Adsorption of Mixtures of a Polycation and Two Different Zwitterionic Surfactants at the Water/Vapor Interface

Abstract: The bulk and interfacial properties of solutions formed by a polycation (i.e., poly(diallyl-dimethylammonium chloride), PDADMAC) and two different zwitterionic surfactants (i.e., coco-betaine (CB) and cocoamidopropyl-betaine (CAPB)) have been studied. The bulk aggregation of the polyelectrolyte and the two surfactants was analyzed by turbidity and electrophoretic mobility measurements, and the adsorption of the solutions at the fluid interface was studied by surface tension and interfacial dilational rheology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
3
23
0
Order By: Relevance
“…Akanno et al 47 suggested the presence of two different regimes for PDADMAC‐zwitterionic surfactant binding. The first one concerns low surfactant concentrations where zwitterionic surfactant molecules bind to the polymer chains.…”
Section: Resultsmentioning
confidence: 99%
“…Akanno et al 47 suggested the presence of two different regimes for PDADMAC‐zwitterionic surfactant binding. The first one concerns low surfactant concentrations where zwitterionic surfactant molecules bind to the polymer chains.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the turbidity of the mixtures for the highest surfactant concentrations can be only explained by the formation of solid particles due to the polyelectrolyte-surfactant association. This is only possible assuming that the formation of kineticallytrapped aggregates occurs due to the Marangoni stresses associated with a local excess of surfactant molecules during the initial stages of the mixing procedure [64][65][66][67][68]. These kinetically-trapped aggregates remain intact upon dilution and present a quasi-neutral inner core formed mainly of surfactant molecules bound to the polymer monomers, where the external region appears positively charged, i.e., formed by non-associated monomers.…”
Section: Pdadmac-surfactant Association In Solutionmentioning
confidence: 99%
“…They have good foaming, detergent and wetting properties and are very mild, presenting excellent dermatological properties; therefore, they are used to reduce the aggressiveness of anionic surfactants. The most common are N-alkyl betaines, derived from trimethylglycine (betaine) [45,46,48].…”
Section: Surfactantsmentioning
confidence: 99%